Pemanfaatan Digital Marketing dalam Memperkenalkan Kawasan Wisata Jalan Tunjungan di Surabaya - Sulistyo Budi Utomo (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
The tourism sector is a very important sector for economic growth both nationally and regionally. Nationally, the tourism sector can contribute 3.5% or $ 4.26 billion of the total gross domestic product (GDP). Within the scope of the East Java region, the tourism sector has contributed IDR 39,408.48 billion. One of the tourist attractions owned by East Java is the Tunjungan Street Area. With the large role of tourism for economic development, digital marketing needs to be done to introduce and attract tourists. This study analyzes the effect of using digital marketing to introduce the Tunjungan Tourism Area using questionnaires and quantitative research. The results of data analysis show that websites and social media have a significant influence on product knowledge and public interest